Effect of Activities on the Value of Chemical Sub-Sector Companies Listed on the Indonesia Stock Exchange - Inrawan, Ady; Eka Putri, Debi; Syahputri, Anggraini; Masyitah, Emi; Lieyadi, Gilbert (Universitas Pamulang, 2024)
The study aims to evaluate two main aspects: first, to provide an overview of activities and company values among Chemical Sub-Sector companies listed on the Indonesia Stock Exchange, and second, to investigate how these activities impact the companies' values. The research design is based on library research, focusing on all Chemical Sub-Sector companies listed as of December 31, 2022. The study employs purposive sampling and combines both qualitative and quantitative descriptive analysis methods. Analytical techniques used include classical assumption tests, simple regression analysis, correlation coefficients, and hypothesis testing. The findings reveal several key points: Firstly, the average level of activity among these companies has shown a tendency to decrease, while their values have generally increased. Secondly, the simple regression analysis indicates that activity does not significantly affect company value, with a negative relationship observed. Thirdly, both the correlation coefficient and determination analysis suggest a very weak relationship between activity levels and company value. Finally, the t-test results confirm that activity has a negative and statistically insignificant impact on company value.